2022
DOI: 10.1073/pnas.2201355119
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical axons regulate neurogenesis and laminar fates in the early sensory cortex

Abstract: Significance This study addresses how the cerebral cortex is partitioned into specialized areas during development. Although both early embryonic patterning and postnatal synaptic input from sensory thalamic nuclei are known to be critical, early roles of thalamic axons in area-specific regulation of cortical neurogenesis are poorly understood. We examined this by developing a genetic mouse model in which thalamocortical projections fail to properly form during embryogenesis, and found these axons ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…More recently, conditional deletion of Gbx2 from the thalamus using Olig3-Cre leads to loss of TCAs reaching the cortex (Fig. 5H; Monko et al 2022). This thalamus-specific manipulation causes a significant reduction in upper layer neurogenesis.…”
Section: Thalamocortical Connectivitymentioning
confidence: 86%
See 1 more Smart Citation
“…More recently, conditional deletion of Gbx2 from the thalamus using Olig3-Cre leads to loss of TCAs reaching the cortex (Fig. 5H; Monko et al 2022). This thalamus-specific manipulation causes a significant reduction in upper layer neurogenesis.…”
Section: Thalamocortical Connectivitymentioning
confidence: 86%
“…This thalamus-specific manipulation causes a significant reduction in upper layer neurogenesis. conditional deletion of Vgf using the same Olig3-Cre approach results in similar phenotypic changes, implicating Vgf as the thalamus-derived diffusible signal carried by TCAs that exerts influence on upper layer neurogenesis (Monko et al 2022;Sato et al 2022). Together, these experiments demonstrate that extrinsic cues from TCAs play an important role in region-specific cortical neurogenesis and laminar development.…”
Section: Thalamocortical Connectivitymentioning
confidence: 96%
“…In the developing brain, thalamic inputs mold the laminar, columnar, and functional organization of the cortex. 99,100 Similarly, more mature thalamic projections might promote organizational maturation in hCOs, and more organized TC assembloids might better model the diversity of synaptic plasticity mechanisms observed across TC sensory pathways. Assembloids modeling other brain structures [101][102][103] (or synaptic targets outside the brain) 104 might also elucidate mechanisms that differ between neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between thalamic axons and cortical progenitors during mouse development are well-documented but are not driven by synaptic connections. [59][60][61] Further analysis revealed that hThO ExNs exhibited a high probability of TC communication with both hCO Cycling Progenitors and Subplate DL/ExNs clusters by NRXN signaling (Figure S6C). However, hThO ExNs exhibited a higher probability of glutamatergic communication with Subplate DL/ExNs than hCO Cycling Progenitors (Figure S6D).…”
Section: Tc Assembloids Form Functional Glutamatergic Tc and Ct Synapsesmentioning
confidence: 99%
“…One of the most wellstudied among these are connections between neurons in the cortex with those in the thalamus (Haber & Calzavara, 2009). In rodents, signals from thalamocortical axons are thought to refine cell morphologies (Li et al, 2013;Narboux-Nême et al, 2012), cell fate (Chou et al, 2013;Pouchelon et al, 2014;Vue et al, 2013), neurogenesis and lamination (Monko et al, 2021), and size (Dehay et al, 1991(Dehay et al, , 2001Reillo et al, 2011), particularly in sensory areas. Further studies will reveal the full scope of intrinsic and extrinsic determinants that define cortical areas, and how they are integrated to produce the complex transcriptomic and phenotypic profiles that delineate these regions.…”
Section: Arealizationmentioning
confidence: 99%